A comparative study of range of motion of forelimb and hind limb in walk pattern and trot pattern of Chihuahua dogs affected and non-affected with Patellar Luxation - Sarisa Klinhom (2018)
© 2015 Academic Journals Inc. The study compared the Ranges of Motion (ROM) of forelimb and hind limb, and the cycle speeds of healthy and Patellar Luxation (PL) dogs in walking and trotting. 21 dogs were divided into three groups: The 5 normal dogs, 6 unilateral PL (PL-1) dogs and 10 bilateral PL (PL-2) dogs. All dogs with PL did not present lameness. The dogs were walking and trotting on a treadmill for the video record. The Kinovea program was employed to evaluate the cycle speed, Maximum Extension Angle (MEA), Maximum Flexion Angle (MFA) and ROM of the shoulder, elbow, carpal, hip, stifle and tarsal joints. The results showed that both the limb sides of the dogs in all the groups in both walking and trotting motions had no significant difference (p > 0.05). It was found that the ROM of the shoulder, carpal, hip and tarsal joints in PL dogs had significant difference (p < 0.05) compared to the normal dog. In conclusion, the unilateral PL limb dogs showed no effect on the opposite limb, the unilateral and the bilateral PL dogs was an effect on the locomotion of the forelimb and the hind limb compared with the normal dogs.